2023
DOI: 10.1084/jem.20221653
|View full text |Cite
|
Sign up to set email alerts
|

IL-21 shapes germinal center polarization via light zone B cell selection and cyclin D3 upregulation

Abstract: Germinal center (GC) dysregulation has been widely reported in the context of autoimmunity. Here, we show that interleukin 21 (IL-21), the archetypal follicular helper T cell (Tfh) cytokine, shapes the scale and polarization of spontaneous chronic autoimmune as well as transient immunization-induced GC. We find that IL-21 receptor deficiency results in smaller GC that are profoundly skewed toward a light zone GC B cell phenotype and that IL-21 plays a key role in selection of light zone GC B cells for entry to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 94 publications
2
15
0
Order By: Relevance
“…It was initially suggested that IL-21 was required for Tfh cell differentiation ( 50 , 51 ), however, subsequent work established that Tfh cells could still form in animals with defective IL-21 signaling ( 25 , 26 , 52 ). Nevertheless, IL-21 has been shown to support Tfh cell expansion and maintenance ( 25 , 53 , 54 ) and it has a marked impact on the ratio of Tfh to follicular regulatory T cells (Tfr) in transient as well as autoimmune GC ( 55 , 56 ).…”
Section: Il-21 Promotes Gc Expansion and Shapes Gc B-cell Polarizationmentioning
confidence: 99%
See 4 more Smart Citations
“…It was initially suggested that IL-21 was required for Tfh cell differentiation ( 50 , 51 ), however, subsequent work established that Tfh cells could still form in animals with defective IL-21 signaling ( 25 , 26 , 52 ). Nevertheless, IL-21 has been shown to support Tfh cell expansion and maintenance ( 25 , 53 , 54 ) and it has a marked impact on the ratio of Tfh to follicular regulatory T cells (Tfr) in transient as well as autoimmune GC ( 55 , 56 ).…”
Section: Il-21 Promotes Gc Expansion and Shapes Gc B-cell Polarizationmentioning
confidence: 99%
“…While GC are typically dominated by dark zone cells in both mice and humans ( 62 , 63 ) several studies have now noted marked skewing towards a light zone phenotype in GC B cells from IL-21- and IL-21R-deficient mice ( Fig. 2 ) ( 46 , 54 , 55 , 57 , 58 , 64 ). Defects in IL-21 signaling have been found to result in impaired dark zone compartments in immunization-induced GC ( 54 , 57 , 58 ) as well as in GC triggered by autoimmunity ( 54 ) and viral infection ( 64 ).…”
Section: Il-21 Promotes Gc Expansion and Shapes Gc B-cell Polarizationmentioning
confidence: 99%
See 3 more Smart Citations